Design optimization of rib/channel patterns in a PEMFC through performance heterogeneities modelling. (3rd May 2018) - Randrianarizafy, Bolahaga; Schott, Pascal; Chandesris, Marion; Gerard, Mathias; Bultel, Yann
Abstract: In this paper, an approach coupling an along the channel and rib-channel models has been developed to perform a design optimization of PEM fuel cell bipolar plates rib/channel patterns. Overall performance mainly results from a competition between current collection and oxygen supply. The allows proposed to investigate the effect of geometry and operating parameters on the resulting equilibrium and optimum. Moreover, heterogeneities issued from the crushing effect by the rib on the GDL are accounted. The electrochemical parameters used in the model are fitted to experimental measurements before being used in the optimization process. Results at the channel/rib scale show the competition between the oxygen supply from the gas channel to the catalyst layer and the current collection by the ribs. This understanding is possible thanks to the access to local conditions (such as the oxygen concentration) given by the model which are difficult to reach with experimental measurements. In-plane and through plane heterogeneities of current density distribution in the catalyst layer are exhibited. Design optimization is performed on the channel width/total width ratio on the cathode side. The model suggests an optimal channel design by varying its width along the flow while the standard design considers a contant ratio. This optimal channel is shown to be mainly dependent on the stoichiometry ratio of oxygen. Highlights: Validated 2D PEMFC models used to monitor local conditions. Models investigate the competition between current collection and oxygen supply. Design optimization is performed on the channel width/total width ratio. Parameters vary as function of the crushing effect of the rib. An optimal channel with a varying width is suggested.